Kant e la 'scuola di Gottinga'. Alcune note a margine della 'tesi Lenoir' (Lebenswelt. Aesthetics and philosophy of experience., 2016)
The paper focuses on the reception of Kant’s philosophy of biology in the context of the so-called ‘Göttingen School’. Timothy Lenoir has tried to rehabilitate the framework elaborated at Göttingen by stressing its difference from Naturphilosophie. Focusing on the work of Karl Friedrich Kielmeyer this paper argues that Lenoir’s position is based on a historiographical bias. I take into account Kielmeyer’s stance on physiology, embryology and natural history. This analysis reveals the existence of a clear shift from a regulative to a constitutive understanding of teleology. I agree with Zammito that the ‘Lenoir thesis’ should be overcome in favor of  a more accurate narrative of the emergence of biology in Germany at the turn of the nineteenth century.